Zinc(ii) centered biologically active novel N, N, O donor tridentate water-soluble hydrazide-based O-carboxymethyl chitosan Schiff base metal complexes: synthesis and characterisation. (3rd June 2019) - Murugaiyan, Manimohan; Mani, S. Pugal; Sithique, Mohamed Aboobucker
Abstract : In this study, novel eco-friendly and water-soluble chitosan Schiff base derivatives have been designed for potential use in antimicrobial applications. Abstract : In this study, novel eco-friendly and water-soluble chitosan Schiff base derivatives have been designed for potential use in antimicrobial applications. The novel water-soluble hydrazide-based O -carboxymethyl chitosan Schiff bases were prepared by carboxymethylation for potential applications in several biomedical and pharmaceutical avenues. Problems relating to the water solubility of hydrazide-based chitosan Schiff base derivatives have been eliminated. Thermogravimetric analysis (TGA) reveals the extended thermal stability of the complex even at an elevated temperature. The X-ray diffraction (XRD) studies reveal crystallinity that is destroyed after complexation. The scanning electron microscopy (SEM) images clearly reveal the crystalline and amorphous nature of the synthesized derivatives. The amorphous form finds wide applications in biological, pharmaceutical and biomedical fields. The synthesized water-soluble chitosan Schiff base derivatives and their metal complexes have been investigated for some biological and pharmacological applications and the studies have shown better antibacterial activity, antifungal assay, anti-inflammatory activity and total antioxidant nature of the complexes.